KEBEBASAN HAKIM PENGADILAN HUBUNGAN INDUSTRIAL DALAM MEMUTUS PERKARA ATAS TUNTUTAN SUBSAIDER EX AEQUO ET BONO - Sihombing, Daniel Romi (JURNAL HUKUM DAS SOLLEN, 2023)
The freedom of judges in deciding a case is part of the judicial authority. Judicial power is the power of an independent state to administer the judiciary in order to uphold law and justice based on Pancasila and Article 24 of the 1945 Constitution, for the sake of implementing the constitutional state of the Republic of Indonesia. Judges in carrying out their judicial power duties must not be tied to anything and / or pressured by anyone. Judges in Indonesia implement the meaning of freedom of judges as a freedom that is responsible, freedom in the corridor of law and order in the prevailing laws and regulations by carrying out the main duties of judicial power in accordance with applicable procedural law and statutory regulations without being influenced by the government or parties. who may have an interest. This study aims to explain the role of judges in examining, hearing and making decisions that are fair or at least close to justice. The judge's Industrial Relation decision on the basis of ex aequo et bono is one of the cases in which the judge does not grant the claim (petitum primair) but for the sake of justice the judge grants the demands (petitum subsidair) ex aequo et bono "if the panel of judges has a different opinion, ask for a fairest decision ( ex aequo et bono)"